Clinical Characteristics of Patients Presenting with Headache at Binocular Vision Clinic: A Hospital Based Study: Doi: 10.36351/pjo.v36i3.1046 - Alrasheed, Saif Hassan (Pakistan Journal of Ophthalmology, 2020)
Purpose: To assess the clinical characteristics of patients presenting with headache at binocular vision clinic. Place and Duration of Study: Al-Neelain eye hospital, Sudan, from February to October 2018. Study Design: Cross-sectional study. Material and Methods: One hundred fifty patients with history of headache were included in study. Dissociated heterophoria was measured using Maddox Wing and Maddox Rod. Associated heterophoria was assessed by the Mallett unit fixation disparity and fusional vergence was measured using a prism bar. The relationship between measures was determined using the chi-squared analysis. For all statistical determinations, significance levels were set at p < 0.05. Results: Mean age was 25 ± 3.5 years. Females constituted 78% and headache was significantly associated with females (P < 0.0001). Majority of patients (82%) presented with exophoria (mean = 4.74 ± 0.75 ? Base-In) at near fixation, 10.7% were orthophoric and 7.34percentage were esophoric (mean = 3.24 ± 0.5 ? Base-Out). The association between near heterophoria and headache was statically significant (?2 = 7.426; p = 0.001). Association between distance heterophoria and headache was not statistically significant (?2 = 22.172; p = 0.265). The association between headache and positive fusional vergence at near fixation was statically significant (p = 0.03). Leading cause of headache was convergence weakness exophoria (39.3%; p = 0.001), followed by convergence insufficiency (24%; p = 0.02). Conclusion: Headache was more common in females and was associated with exophoria, convergence insufficiency and inadequate positive fusional vergence at near fixation